High-toughness modified petg copolyester composite material for 3D printing and preparation method thereof

CN122563301BActive Publication Date: 2026-10-16BO WO ENVIRONMENTAL PROTECTION TECH (WUHAN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611062798.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-16
Estimated Expiration
2046-07-17

AI Technical Summary

Technical Problem

[0005]针对上述问题,本发明的目的在于提供一种用于3D打印的高韧性改性PETG共聚酯复合材料及其制备方法,以改善现有PETG共聚酯材料在高韧化改性后容易出现的喷口拉丝、挤出稳定性下降、层间抗裂性不足或尺寸稳定性难以兼顾的问题

Benefits of technology

[0067] This invention constructs a flexible bridging interface by grafting carboxylated cellulose nanocrystals with polycaprolactone, so that the cellulose nanocrystals no longer exist as rigid fillers in the PETG matrix, which helps to reduce the risk of embrittlement caused by nanocrystal agglomeration and stress concentration at the rigid interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122563301B_ABST
    Figure CN122563301B_ABST
Patent Text Reader

Abstract

The application provides a high-toughness modified PETG copolyester composite material for 3D printing and a preparation method thereof, and belongs to the technical field of high polymer composite materials. The composite material takes PETG resin as a main body, introduces PCL-based thermoplastic polyurethane, pre-dispersed master batch containing polycaprolactone grafted carboxylated cellulose nanocrystals, epoxy functionalized chain extender, carbon diimide hydrolysis-resistant agent, antioxidant and acetylacetone zinc, and is prepared through melt blending and wire extrusion. The system uses the cooperation of flexible energy-absorbing phase, modified cellulose nanocrystal interface support, epoxy chain extension bridge and low-dose zinc salt interface adjustment to improve the problems of easy wire drawing, insufficient interlayer bonding and decreased wire forming stability of PETG after high-toughening, and is suitable for FDM / FFF 3D printing wire preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer composite materials technology, and relates to a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method. Background Technology

[0002] PETG copolyester (polyethylene terephthalate-1,4-cyclohexanediethanol copolyester) is a type of thermoplastic polyester material commonly used in fused deposition modeling (FDM) 3D printing. It possesses good transparency, processing flowability, interlayer adhesion, and low shrinkage. Compared to materials like PLA, PETG offers advantages in toughness, chemical resistance, and the stability of printed products, thus it is widely used in the printing of functional prototypes, fixtures, housings, connectors, and general structural components.

[0003] However, for 3D printed parts that need to withstand impact, bending, assembly stress, or repeated stress, there is still room for improvement in the toughness and interlayer crack resistance of ordinary PETG materials. Current technologies typically modify PETG by adding elastomers, chain extenders, or inorganic fillers. The addition of elastomers helps improve the material's impact energy absorption capacity, but increasing the dosage may lead to increased melt elasticity, heavier nozzle drawing, decreased filament stiffness, or reduced dimensional stability. Chain extenders can improve the melt strength of polyester materials, but improper use may also cause increased melt viscosity, increased extrusion pressure, or a narrower processing window. Inorganic or cellulose fillers can improve support and dimensional retention, but if they are not sufficiently compatible with the PETG matrix interface, they are prone to agglomeration or the formation of stress concentration points.

[0004] Furthermore, the FDM printing process differs from conventional injection molding. The material must simultaneously undergo high-shear extrusion within the nozzle, low-shear filament breakage at the nozzle, and thermal contact and interlayer fusion between adjacent layers. Existing PETG modification systems often focus on improving the material's bulk toughness, while neglecting the balance between extrusion stability, filament pull control, and interlayer crack resistance during the printing process. This results in printed products that struggle to achieve optimal impact toughness, Z-axis interlayer bonding, surface finish quality, and dimensional stability. Summary of the Invention

[0005] To address the aforementioned problems, the present invention aims to provide a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method, thereby improving the problems that existing PETG copolyester materials easily encounter after high-toughness modification, such as nozzle stringing, decreased extrusion stability, insufficient interlayer crack resistance, or difficulty in simultaneously achieving dimensional stability.

[0006] To achieve this objective, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing a high-toughness modified PETG copolyester composite material for 3D printing, the method comprising:

[0008] S1: Cellulose nanocrystals were vacuum dried and dispersed in anhydrous N-methylpyrrolidone to obtain a dispersion. After shear dispersion, maleic anhydride and 4-dimethylaminopyridine were added to obtain reaction solution A. The reaction was mechanically stirred under nitrogen protection. After washing with anhydrous ethanol and acetone alternately, centrifuging, and vacuum drying for a second time, maleic anhydride-modified cellulose nanocrystals were obtained. The maleic anhydride-modified cellulose nanocrystals were redispersed in anhydrous N-methylpyrrolidone and ultrasonically dispersed. ε-caprolactone monomer and stannous octoate catalyst were added to obtain reaction solution B. The reaction was mechanically stirred under nitrogen protection. After washing with anhydrous ethanol and acetone alternately, centrifuging, and vacuum drying for a third time, the nanocrystals were ground and sieved to obtain polycaprolactone-grafted carboxylated cellulose nanocrystals.

[0009] S2: PETG resin particles, polycaprolactone-grafted carboxylated cellulose nanocrystals, antioxidant 1010 and antioxidant 168 are premixed to obtain a premix; the premix is ​​fed into a co-rotating twin-screw extruder and vacuum exhaust is turned on. After melt extrusion, water cooling and pelletizing, and vacuum drying, modified cellulose nanocrystal predispersed masterbatch is obtained.

[0010] S3: PETG resin particles, PCL (poly(ε-caprolactone))-based thermoplastic polyurethane, and modified cellulose nanocrystal pre-dispersed masterbatch are dried and mixed separately. Epoxy functionalized chain extender, carbodiimide anti-hydrolysis agent, and antioxidant are added and mixed to obtain a mixed raw material. During the mixing process, zinc acetylacetone dispersion is sprayed. The zinc acetylacetone dispersion is obtained by dispersing zinc acetylacetone in a mixed solvent. The mixed raw material is added to a twin-screw extruder, melt-blended, extruded, cooled, and pelletized to obtain high-toughness modified PETG copolyester composite particles.

[0011] S4: High-toughness modified PETG copolyester composite particles are placed in the hopper of a precision single-screw wire extruder. After the melt is extruded through the round die, it enters a constant temperature water bath for cooling and shaping to obtain wire. After removing surface moisture through a dehumidifying hot air drying device, it is vacuum dried and then wound up to obtain a high-toughness modified PETG copolyester composite material for 3D printing.

[0012] As a preferred technical solution of the present invention, in step S1, the temperature for vacuum drying of the cellulose nanocrystals is 60-80℃, for example, it can be 60℃, 62℃, 64℃, 66℃, 68℃, 70℃, 72℃, 74℃, 76℃, 78℃ or 80℃, but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0013] In some optional embodiments, the vacuum drying time of the cellulose nanocrystals is 12-24 hours, for example, 12 hours, 13.2 hours, 14.4 hours, 15.6 hours, 16.8 hours, 18 hours, 19.2 hours, 20.4 hours, 21.6 hours, 22.8 hours, or 24 hours, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0014] In some optional embodiments, the mass-to-volume ratio of the cellulose nanocrystals to anhydrous N-methylpyrrolidone is 1 g:(20-50) mL, for example, 1 g:20 mL, 1 g:23 mL, 1 g:26 mL, 1 g:29 mL, 1 g:32 mL, 1 g:35 mL, 1 g:38 mL, 1 g:41 mL, 1 g:44 mL, 1 g:47 mL, or 1 g:50 mL, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0015] In some optional embodiments, the rotational speed of the dispersion shear is 5000-10000 rpm, for example, it can be 5000 rpm, 5500 rpm, 6000 rpm, 6500 rpm, 7000 rpm, 7500 rpm, 8000 rpm, 8500 rpm, 9000 rpm, 9500 rpm or 10000 rpm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0016] In some optional embodiments, the shear dispersion time of the dispersion is 10-30 min, for example, it can be 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0017] In some optional embodiments, the mass ratio of maleic anhydride to cellulose nanocrystals is (0.03-0.15):1, for example, it can be 0.03:1, 0.042:1, 0.054:1, 0.066:1, 0.078:1, 0.09:1, 0.102:1, 0.114:1, 0.126:1, 0.138:1 or 0.15:1, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0018] In some optional embodiments, the mass ratio of 4-dimethylaminopyridine to maleic anhydride is 1:(20-100), for example, 1:20, 1:28, 1:36, 1:44, 1:52, 1:60, 1:68, 1:76, 1:84, 1:92 or 1:100, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0019] In some optional embodiments, the temperature of the mechanically stirred reaction of the reaction solution A is 100-115°C, for example, it can be 100°C, 101.5°C, 103°C, 104.5°C, 106°C, 107.5°C, 109°C, 110.5°C, 112°C, 113.5°C or 115°C, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0020] In some optional embodiments, the reaction time of the reaction solution A by mechanical stirring is 2-4 hours, for example, it can be 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0021] In some optional embodiments, the reaction solution A is washed 3-5 times after the reaction, for example, 3, 4 or 5 times, but not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0022] In some optional embodiments, the temperature of the second vacuum drying is 60-80°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0023] In some optional embodiments, the second vacuum drying time is 8-12 hours, for example, 8 hours, 8.4 hours, 8.8 hours, 9.2 hours, 9.6 hours, 10 hours, 10.4 hours, 10.8 hours, 11.2 hours, 11.6 hours or 12 hours, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0024] In some optional embodiments, the mass-to-volume ratio of the maleic anhydride cellulose nanocrystals to anhydrous N-methylpyrrolidone is 1 g:(20-50) mL, for example, 1 g:20 mL, 1 g:23 mL, 1 g:26 mL, 1 g:29 mL, 1 g:32 mL, 1 g:35 mL, 1 g:38 mL, 1 g:41 mL, 1 g:44 mL, 1 g:47 mL, or 1 g:50 mL, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0025] In some optional embodiments, the ultrasonic dispersion time is 10-20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0026] In some optional embodiments, the mass ratio of ε-caprolactone to maleic anhydride-modified cellulose nanocrystals is (0.8-2.0):1, for example, it can be 0.8:1, 0.92:1, 1.04:1, 1.16:1, 1.28:1, 1.4:1, 1.52:1, 1.64:1, 1.76:1, 1.88:1 or 2.0:1, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0027] In some optional embodiments, the mass ratio of stannous octoate to ε-caprolactone monomer is 1:(200-1000), for example, it can be 1:200, 1:280, 1:360, 1:440, 1:520, 1:600, 1:680, 1:760, 1:840, 1:920 or 1:1000, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0028] In some optional embodiments, the temperature of the mechanically stirred reaction of the reaction solution B is 115-130°C, for example, 115°C, 116.5°C, 118°C, 119.5°C, 121°C, 122.5°C, 124°C, 125.5°C, 127°C, 128.5°C or 130°C, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0029] In some optional embodiments, the reaction time of the reaction solution B by mechanical stirring is 4-8 hours, for example, it can be 4 hours, 4.4 hours, 4.8 hours, 5.2 hours, 5.6 hours, 6 hours, 6.4 hours, 6.8 hours, 7.2 hours, 7.6 hours or 8 hours, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0030] In some optional embodiments, the reaction solution B is washed 3-5 times after the reaction, for example, 3, 4 or 5 times, but not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0031] In some optional embodiments, the temperature of the third vacuum drying is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0032] In some optional embodiments, the third vacuum drying time is 12-24 hours, for example, 12 hours, 13.2 hours, 14.4 hours, 15.6 hours, 16.8 hours, 18 hours, 19.2 hours, 20.4 hours, 21.6 hours, 22.8 hours or 24 hours, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0033] In some optional embodiments, the mesh size of the sieve used for sieving is 200-400 mesh, for example, it can be 200 mesh, 220 mesh, 240 mesh, 260 mesh, 280 mesh, 300 mesh, 320 mesh, 340 mesh, 360 mesh, 380 mesh or 400 mesh, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0034] As a preferred technical solution of the present invention, in step S2, the mass ratio of the PETG resin particles, polycaprolactone-grafted carboxylated cellulose nanocrystals, antioxidant 1010 and antioxidant 168 is 100:(20-30):(0.1-0.3):(0.1-0.3), for example, it can be 100:(20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30):(0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28 or 0.3):(0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28 or 0.3), but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0035] In some optional embodiments, the screw speed of the twin-screw extruder is 250-270 rpm, for example, 250 rpm, 252 rpm, 254 rpm, 256 rpm, 258 rpm, 260 rpm, 262 rpm, 264 rpm, 266 rpm, 268 rpm or 270 rpm, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0036] In some optional embodiments, the extrusion temperature of the twin-screw extruder is 215-225°C, for example, 215°C, 216°C, 217°C, 218°C, 219°C, 220°C, 221°C, 222°C, 223°C, 224°C or 225°C, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0037] In some optional embodiments, the die temperature of the twin-screw extruder is 220-230°C, for example, 220°C, 221°C, 222°C, 223°C, 224°C, 225°C, 226°C, 227°C, 228°C, 229°C or 230°C, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0038] In some optional embodiments, the vacuum exhaust pressure is -0.09 to -0.06 MPa, for example, it can be -0.09 MPa, -0.087 MPa, -0.084 MPa, -0.081 MPa, -0.078 MPa, -0.075 MPa, -0.072 MPa, -0.069 MPa, -0.066 MPa, -0.063 MPa or -0.06 MPa, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0039] In some optional embodiments, the vacuum drying temperature is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0040] In some optional embodiments, the vacuum drying time is 8-10 hours, for example, 8 hours, 8.2 hours, 8.4 hours, 8.6 hours, 8.8 hours, 9 hours, 9.2 hours, 9.4 hours, 9.6 hours, 9.8 hours, or 10 hours, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0041] As a preferred technical solution of the present invention, in step S3, the drying temperature of the PETG resin particles, PCL-based thermoplastic polyurethane and modified cellulose nanocrystal pre-dispersed masterbatch is 70-80℃, for example, it can be 70℃, 71℃, 72℃, 73℃, 74℃, 75℃, 76℃, 77℃, 78℃, 79℃ or 80℃, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0042] In some optional embodiments, the drying time of the PETG resin particles, PCL-based thermoplastic polyurethane, and modified cellulose nanocrystal predispersed masterbatch is 6-8 hours, for example, 6 hours, 6.2 hours, 6.4 hours, 6.6 hours, 6.8 hours, 7 hours, 7.2 hours, 7.4 hours, 7.6 hours, 7.8 hours, or 8 hours, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0043] The PCL-based thermoplastic polyurethane is preferably Pearlthane® 11T85.

[0044] The epoxy functionalized chain extender is any one of Joncryl® ADR 4468, Joncryl® ADR 4368, Joncryl® ADR 4400, or Joncryl® ADR 4380.

[0045] The carbodiimide antihydrolysis agent is any one of Stabaxol® P 100, Stabaxol® P 200, or Stabaxol® I.

[0046] The antioxidant is any one of antioxidant 1010, antioxidant 168, or antioxidant 1076.

[0047] The volume ratio of ethanol to acetone in the mixed solvent is 1:3.

[0048] In some optional embodiments, the mass-to-volume ratio of zinc acetylacetonate to the mixed solvent is 1 g:(80-120) mL, for example, it can be 1 g:80 mL, 1 g:84 mL, 1 g:88 mL, 1 g:92 mL, 1 g:96 mL, 1 g:100 mL, 1 g:104 mL, 1 g:108 mL, 1 g:112 mL, 1 g:116 mL or 1 g:120 mL, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0049] In some alternative embodiments, the screw speed of the twin-screw extruder is 220-280 rpm, for example, 220 rpm, 226 rpm, 232 rpm, 238 rpm, 244 rpm, 250 rpm, 256 rpm, 262 rpm, 268 rpm, 274 rpm, or 280 rpm, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0050] In some optional embodiments, the extrusion temperature of the twin-screw extruder is 220-235°C, for example, 220°C, 221.5°C, 223°C, 224.5°C, 226°C, 227.5°C, 229°C, 230.5°C, 232°C, 233.5°C, or 235°C, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0051] In some optional embodiments, the die temperature of the twin-screw extruder is 225-240°C, for example, 225°C, 226.5°C, 228°C, 229.5°C, 231°C, 232.5°C, 234°C, 235.5°C, 237°C, 238.5°C, or 240°C, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0052] In some optional embodiments, the mass ratio of the PETG resin particles, PCL-based thermoplastic polyurethane, modified cellulose nanocrystal predispersed masterbatch, epoxy functionalized chain extender, carbodiimide anti-hydrolysis agent, antioxidant, and zinc acetylacetonate is (80-90):(3-8):(10-20):(0.2-0.5):(0.1-0.2):(0.2-0.4):(0.03-0.12), for example, it can be (80, 81, 82, 83, 84, 85, 86, 87, 88, 89 or 90):(3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8):(10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20):(0. 2. 0.23, 0.26, 0.29, 0.32, 0.35, 0.38, 0.41, 0.44, 0.47 or 0.5: (0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19 or 0.2): (0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, 0.34, 0.36, 0.38 or 0.4): (0.03, 0.039, 0.048, 0.057, 0.066, 0.075, 0.084, 0.093, 0.102, 0.111 or 0.12), but not limited to the listed values; other unlisted values ​​within this range also apply.

[0053] As a preferred technical solution of the present invention, in step S4, the extrusion section temperature of the single-screw wire extruder is 210-235℃, for example, it can be 210℃, 212.5℃, 215℃, 217.5℃, 220℃, 222.5℃, 225℃, 227.5℃, 230℃, 232.5℃ or 235℃, but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0054] In some optional embodiments, the die temperature of the single-screw wire extruder is 220-235°C, for example, 220°C, 221.5°C, 223°C, 224.5°C, 226°C, 227.5°C, 229°C, 230.5°C, 232°C, 233.5°C, or 235°C, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0055] In some optional embodiments, the screw speed of the single-screw wire extruder is 15-40 rpm, for example, it can be 15 rpm, 17.5 rpm, 20 rpm, 22.5 rpm, 25 rpm, 27.5 rpm, 30 rpm, 32.5 rpm, 35 rpm, 37.5 rpm or 40 rpm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0056] In some optional embodiments, the diameter of the circular die head is 2.0-2.5 mm, for example, it can be 2.0 mm, 2.05 mm, 2.1 mm, 2.15 mm, 2.2 mm, 2.25 mm, 2.3 mm, 2.35 mm, 2.4 mm, 2.45 mm or 2.5 mm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0057] In some optional embodiments, the temperature of the constant temperature water bath is 15-30°C, for example, it can be 15°C, 16.5°C, 18°C, 19.5°C, 21°C, 22.5°C, 24°C, 25.5°C, 27°C, 28.5°C or 30°C, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0058] In some optional embodiments, the vacuum drying temperature is 60-70°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0059] In some optional embodiments, the vacuum drying time is 4-8 hours, for example, 4 hours, 4.4 hours, 4.8 hours, 5.2 hours, 5.6 hours, 6 hours, 6.4 hours, 6.8 hours, 7.2 hours, 7.6 hours or 8 hours, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0060] In a second aspect, the present invention provides a high-toughness modified PETG copolyester composite material for 3D printing, which is prepared by the preparation method described in the first aspect.

[0061] The performance of PETG composite materials for FDM printing depends not only on the toughness of the material itself, but also on the continuous processing, including high-shear extrusion at the nozzle, low-shear filament breakage at the nozzle, and interlayer thermal contact healing. In existing PETG toughening systems, simply increasing the elastomer content, while beneficial for absorbing impact energy, can easily increase melt elasticity, exacerbate nozzle filament pulling, and potentially reduce filament stiffness and dimensional retention. Conversely, simply adding rigid nanofillers, while improving melt support, can easily lead to agglomeration points or stress concentration points due to insufficient interfacial compatibility, thus weakening the crack resistance of the printed parts. This invention achieves a better balance between toughening, filament breakage, interlayer bonding, and processing stability in the composite material through the combination of PCL-based thermoplastic polyurethane, polycaprolactone-grafted carboxylated cellulose nanocrystals, epoxy-functionalized chain extenders, carbodiimide anti-hydrolysis agents, antioxidants, and zinc acetylacetonate.

[0062] In this system, PCL-based thermoplastic polyurethane, as a flexible energy-absorbing phase, is mainly used to alleviate the brittle cracking tendency of PETG under impact or bending loads. However, its dosage is controlled within a low range to avoid slowing down melt low-shear relaxation, reducing wire stiffness, or decreasing dimensional stability due to excessive flexible phase. Polycaprolactone-grafted carboxylated cellulose nanocrystals play a role in interface regulation and rheological support: cellulose nanocrystals have a certain rigidity and aspect ratio, which helps to form a certain orientation and support under melt extrusion shear, thereby improving the shape retention of the wire after extrusion and deposition; the polycaprolactone segments grafted on its surface can form a flexible transition layer between cellulose nanocrystals and PETG and PCL-based thermoplastic polyurethane, reducing the interfacial stress concentration that may be caused by the direct introduction of rigid nanocrystals; its carboxylated structure can provide active sites for subsequent interfacial reactions with epoxy functionalized chain extenders and help improve the interfacial bonding between modified cellulose nanocrystals and polyester matrix.

[0063] During the high-shear extrusion stage, the modified cellulose nanocrystals exhibit a certain orientation along the melt flow direction. Combined with the buffering effect of the polycaprolactone flexible segments at the interface, this helps improve the flow continuity of the composite melt and reduces the risk of localized blockage and extrusion fluctuations caused by nano-component agglomeration. During the nozzle cessation extrusion or low-shear fiber breakage stage, the weak physical support structure formed between the modified cellulose nanocrystals and the polyester matrix helps improve melt retraction and low-shear support capabilities, thereby alleviating problems such as fiber pulling, material snagging, or edge smearing caused by elastomer toughening. This process does not rely on a single component but is achieved through a combination of energy absorption by a low proportion of flexible phase, support provided by modified cellulose nanocrystals, and flexible bridging provided by polycaprolactone segments.

[0064] During the interlayer thermal healing stage, the interfacial contact time between the newly deposited melt and the already deposited layer is short. If the toughening phase or filler hinders the diffusion of PETG segments, it can easily lead to insufficient improvement in bulk toughness but insufficient improvement in interlayer crack resistance. In this invention, the epoxy functionalized chain extender, as a reactive interfacial modifier, can participate in the end-group regulation and interfacial bridging between PETG end groups, polycaprolactone segment end groups, and polycaprolactone-grafted carboxylated cellulose nanocrystals during melt blending, which helps to improve the interfacial bonding between the PETG matrix, the flexible phase, and the modified cellulose nanocrystals. Zinc acetylacetonate, present in a low dose, participates in the thermal processing of the composite system as an interfacial modifier during melt processing and interlayer thermal contact, which helps to improve the contact fusion and interfacial reforming conditions of polyester segments at the interlayer interface. Through the combination of end-group regulation, interfacial bridging, and interlayer interfacial contact fusion, the stability of interlayer bonding is improved.

[0065] The addition of carbodiimide anti-hydrolysis agents and antioxidants primarily reduces the risk of hydrolysis and thermo-oxidative degradation of PETG, PCL segments, and PCL-based thermoplastic polyurethane during twin-screw extrusion, wire extrusion, and subsequent secondary heating during printing. This ensures the relative stability of the interfacial structure constructed by epoxy chain extenders, zinc acetylacetonate, and modified cellulose nanocrystals during processing. Therefore, this invention does not simply improve PETG performance by adding elastomers or rigid fillers. Instead, it achieves a synergistic effect through flexible energy-absorbing phases, flexible bridging nanocrystals, reactive interfacial bridging components, and low-dose zinc salt interfacial conditioning components. This results in relatively matched rheological and interfacial responses in the three stages of high-shear extrusion, low-shear filament breakage, and interlayer thermal healing, thus addressing the challenge of balancing high toughness with printing stability and interlayer crack resistance.

[0066] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0067] This invention constructs a flexible bridging interface by grafting carboxylated cellulose nanocrystals with polycaprolactone, so that the cellulose nanocrystals no longer exist as rigid fillers in the PETG matrix, which helps to reduce the risk of embrittlement caused by nanocrystal agglomeration and stress concentration at the rigid interface.

[0068] This invention controls the amount of PCL-based thermoplastic polyurethane within a low range and combines it with modified cellulose nanocrystal pre-dispersed masterbatch, so that the material can obtain flexible energy absorption while still maintaining good wire stiffness and melt support, which is beneficial to improving the balance between high toughness and printing stability.

[0069] This invention combines epoxy functionalized chain extenders, carbodiimide anti-hydrolysis agents, antioxidants, and zinc acetylacetonate to balance interfacial bonding, secondary thermal processing stability, and interlayer interfacial contact fusion, thereby improving the interlayer bonding stability and crack resistance of printed products. Attached Figure Description

[0070] Figure 1 This is a flowchart of the preparation method of the high-toughness modified PETG copolyester composite material for 3D printing described in this application. Detailed Implementation

[0071] The technical solutions of the present invention will be described in detail below with reference to specific embodiments and accompanying drawings. The embodiments described herein are specific implementations of the present invention, used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary, and should not be construed as limiting the implementation methods or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can employ other obvious technical solutions based on the content disclosed in the claims and specification of this application. These technical solutions include any obvious substitutions and modifications made to the embodiments described herein.

[0072] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone further purification or processing.

[0073] Example 1

[0074] This embodiment provides a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method. The preparation method specifically includes the following steps:

[0075] S1: Cellulose nanocrystals were vacuum dried at 75℃ for 20 h and then dispersed in anhydrous N-methylpyrrolidone to obtain a dispersion, wherein the mass-to-volume ratio of cellulose nanocrystals to anhydrous N-methylpyrrolidone was 1 g: 40 mL; after shearing and dispersion at 9000 rpm for 25 min, maleic anhydride and 4-dimethylaminopyridine were added to obtain reaction solution A, wherein the mass ratio of maleic anhydride to cellulose nanocrystals was 0.12:1 and the mass ratio of 4-dimethylaminopyridine to maleic anhydride was 1:80. The reaction was mechanically stirred at 105℃ for 3.5 h under nitrogen protection; after washing with anhydrous ethanol and acetone alternately 4 times, centrifuging, and vacuum drying at 65℃ for 9 h, maleic anhydride-modified cellulose nanocrystals were obtained. Maleic anhydride-modified cellulose nanocrystals were redispersed in anhydrous N-methylpyrrolidone, with a mass-to-volume ratio of maleic anhydride-modified cellulose nanocrystals to anhydrous N-methylpyrrolidone of 1 g:35 mL. After ultrasonic dispersion for 18 min, ε-caprolactone monomer and stannous octoate catalyst were added to obtain reaction solution B, with a mass ratio of ε-caprolactone to maleic anhydride-modified cellulose nanocrystals of 1.2:1 and a mass ratio of stannous octoate to ε-caprolactone monomer of 1:800. The reaction was carried out under nitrogen protection at 125 °C with mechanical stirring for 7 h. After washing with anhydrous ethanol and acetone four times alternately, centrifuging, and vacuum drying at 75 °C for 20 h, the nanocrystals were obtained by grinding and passing through a 350-mesh sieve.

[0076] S2: PETG resin particles, polycaprolactone-grafted carboxylated cellulose nanocrystals, antioxidant 1010 and antioxidant 168 were premixed at a mass ratio of 100:28:0.25:0.22 to obtain a premix; the premix was fed into a co-rotating twin-screw extruder at a screw speed of 265 rpm, an extrusion temperature of 218℃, a die head temperature of 228℃, and vacuum exhaust was turned on at a vacuum exhaust pressure of -0.08 MPa. After melt extrusion, water cooling, pelletizing, and vacuum drying at 78℃ for 9.5 h, modified cellulose nanocrystal predispersed masterbatch was obtained.

[0077] S3: PETG resin particles, PCL-based thermoplastic polyurethane Pearlthane® 11T85, and modified cellulose nanocrystal pre-dispersed masterbatch were dried at 72°C for 7.5 hours and then mixed. The epoxy functionalized chain extender Joncryl® ADR4400 and the carbodiimide anti-hydrolysis agent Stabaxol® were then added. I. Antioxidant 1010 is mixed to obtain a mixed raw material, and an acetylacetone zinc dispersion is sprayed during the mixing process. The acetylacetone zinc dispersion is obtained by dispersing acetylacetone zinc in a mixed solvent, wherein the volume ratio of ethanol to acetone in the mixed solvent is 1:3, and the mass-volume ratio of acetylacetone zinc to the mixed solvent is 1g:110mL. The mixed raw material is added to a twin-screw extruder with a screw speed of 260rpm, an extrusion temperature of 230℃, and a die temperature of 235℃. After melt blending extrusion, cooling, and pelletizing, high-toughness modified PETG copolyester composite particles are obtained. The mass ratio of PETG resin particles, PCL-based thermoplastic polyurethane, modified cellulose nanocrystal pre-dispersed masterbatch, epoxy functionalized chain extender, carbodiimide anti-hydrolysis agent, antioxidant, and acetylacetone zinc is 88:7:18:0.4:0.18:0.35:0.1.

[0078] S4: High-toughness modified PETG copolyester composite particles are placed in the hopper of a precision single-screw wire extruder. The extrusion section temperature is set to 230℃, the die temperature to 230℃, and the screw speed to 30rpm. After the melt is extruded through a 2.4mm diameter round die, it enters a 28℃ constant temperature water bath for cooling and shaping to obtain wire. After removing surface moisture through a dehumidifying hot air drying device, it is vacuum dried at 68℃ for 7 hours. Then, the wire is wound up to obtain a high-toughness modified PETG copolyester composite material for 3D printing.

[0079] Example 2

[0080] This embodiment provides a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method. The preparation method specifically includes the following steps:

[0081] S1: Cellulose nanocrystals were vacuum dried at 60℃ for 24 h, then dispersed in anhydrous N-methylpyrrolidone to obtain a dispersion, wherein the mass-to-volume ratio of cellulose nanocrystals to anhydrous N-methylpyrrolidone was 1 g: 50 mL; after shearing and dispersion at 5000 rpm for 10 min, maleic anhydride and 4-dimethylaminopyridine were added to obtain reaction solution A, wherein the mass ratio of maleic anhydride to cellulose nanocrystals was 0.03:1, and the mass ratio of 4-dimethylaminopyridine to maleic anhydride was 1:100. The reaction was mechanically stirred at 100℃ for 2 h under nitrogen protection; after washing three times alternately with anhydrous ethanol and acetone, centrifuged, and vacuum dried at 80℃ for 8 h, maleic anhydride-modified cellulose nanocrystals were obtained; Maleic anhydride-modified cellulose nanocrystals were redispersed in anhydrous N-methylpyrrolidone, with a mass-to-volume ratio of maleic anhydride-modified cellulose nanocrystals to anhydrous N-methylpyrrolidone of 1 g: 20 mL. After ultrasonic dispersion for 10 min, ε-caprolactone monomer and stannous octoate catalyst were added to obtain reaction solution B, with a mass ratio of ε-caprolactone to maleic anhydride-modified cellulose nanocrystals of 0.8:1 and a mass ratio of stannous octoate to ε-caprolactone monomer of 1:200. The reaction was carried out under nitrogen protection at 130 °C with mechanical stirring for 4 h. After washing five times with anhydrous ethanol and acetone, centrifuging, and vacuum drying at 80 °C for 12 h, the nanocrystals were obtained by grinding and passing through a 400-mesh sieve.

[0082] S2: PETG resin particles, polycaprolactone-grafted carboxylated cellulose nanocrystals, antioxidant 1010 and antioxidant 168 were premixed at a mass ratio of 100:20:0.1:0.3 to obtain a premix; the premix was fed into a co-rotating twin-screw extruder at a screw speed of 270 rpm, an extrusion temperature of 215℃, a die head temperature of 230℃, and vacuum exhaust was turned on at a vacuum exhaust pressure of -0.09 MPa. After melt extrusion, water cooling, pelletizing, and vacuum drying at 70℃ for 8 hours, modified cellulose nanocrystal predispersed masterbatch was obtained.

[0083] S3: PETG resin particles, PCL-based thermoplastic polyurethane Pearlthane® 11T85, and modified cellulose nanocrystal pre-dispersed masterbatch were dried at 80°C for 6 hours and then mixed. The epoxy functionalized chain extender Joncryl® ADR4368 and the carbodiimide anti-hydrolysis agent Stabaxol® P were added. 200 and antioxidant 168 were mixed to obtain a mixed raw material. During the mixing process, a zinc acetylacetone dispersion was sprayed on. The zinc acetylacetone dispersion was obtained by dispersing zinc acetylacetone in a mixed solvent, wherein the volume ratio of ethanol to acetone in the mixed solvent was 1:3, and the mass-volume ratio of zinc acetylacetone to the mixed solvent was 1g:80mL. The mixed raw material was added to a twin-screw extruder with a screw speed of 280rpm, an extrusion temperature of 220℃, and a die temperature of 240℃. After melt blending extrusion, cooling, and pelletizing, high-toughness modified PETG copolyester composite particles were obtained. The mass ratio of PETG resin particles, PCL-based thermoplastic polyurethane, modified cellulose nanocrystal pre-dispersed masterbatch, epoxy functionalized chain extender, carbodiimide anti-hydrolysis agent, antioxidant, and zinc acetylacetone was 90:3:10:0.2:0.2:0.2:0.03.

[0084] S4: High-toughness modified PETG copolyester composite particles are placed in the hopper of a precision single-screw wire extruder. The extrusion section temperature is set to 235℃, the die temperature to 220℃, and the screw speed to 15rpm. After the melt is extruded through a 2.5mm diameter round die, it enters a 15℃ constant temperature water bath for cooling and shaping to obtain wire. After removing surface moisture with a dehumidifying hot air drying device, it is vacuum dried at 70℃ for 4 hours. Then, the wire is wound up to obtain a high-toughness modified PETG copolyester composite material for 3D printing.

[0085] Example 3

[0086] This embodiment provides a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method. The preparation method specifically includes the following steps:

[0087] S1: Cellulose nanocrystals were vacuum dried at 80℃ for 12 h, then dispersed in anhydrous N-methylpyrrolidone to obtain a dispersion, wherein the mass-to-volume ratio of cellulose nanocrystals to anhydrous N-methylpyrrolidone was 1 g: 20 mL; after shearing and dispersion at 10000 rpm for 30 min, maleic anhydride and 4-dimethylaminopyridine were added to obtain reaction solution A, wherein the mass ratio of maleic anhydride to cellulose nanocrystals was 0.15:1, and the mass ratio of 4-dimethylaminopyridine to maleic anhydride was 1:20. The reaction was mechanically stirred at 115℃ for 4 h under nitrogen protection; after washing 5 times alternately with anhydrous ethanol and acetone, centrifuged, and vacuum dried at 60℃ for 12 h, maleic anhydride-modified cellulose nanocrystals were obtained; Maleic anhydride-modified cellulose nanocrystals were redispersed in anhydrous N-methylpyrrolidone, with a mass-to-volume ratio of maleic anhydride-modified cellulose nanocrystals to anhydrous N-methylpyrrolidone of 1 g:50 mL. After ultrasonic dispersion for 20 min, ε-caprolactone monomer and stannous octoate catalyst were added to obtain reaction solution B, with a mass ratio of ε-caprolactone to maleic anhydride-modified cellulose nanocrystals of 2.0:1 and a mass ratio of stannous octoate to ε-caprolactone monomer of 1:1000. The reaction was carried out under nitrogen protection at 115 °C with mechanical stirring for 8 h. After washing three times with anhydrous ethanol and acetone, centrifuging, and vacuum drying at 60 °C for 24 h, the nanocrystals were obtained by grinding and passing through a 200-mesh sieve.

[0088] S2: PETG resin particles, polycaprolactone-grafted carboxylated cellulose nanocrystals, antioxidant 1010 and antioxidant 168 were premixed at a mass ratio of 100:30:0.3:0.1 to obtain a premix; the premix was fed into a co-rotating twin-screw extruder at a screw speed of 250 rpm, an extrusion temperature of 225℃, a die temperature of 220℃, and vacuum exhaust was turned on at a vacuum exhaust pressure of -0.06 MPa. After melt extrusion, water cooling, pelletizing, and vacuum drying at 80℃ for 10 h, modified cellulose nanocrystal predispersed masterbatch was obtained.

[0089] S3: PETG resin particles, PCL-based thermoplastic polyurethane, and modified cellulose nanocrystal pre-dispersed masterbatch were dried at 70℃ for 8 hours and then mixed. The epoxy functionalized chain extender Joncryl® ADR 4380 and the carbodiimide anti-hydrolysis agent Stabaxol® P were added. 200 and antioxidant 1076 were mixed to obtain a mixed raw material. During the mixing process, a zinc acetylacetone dispersion was sprayed on. The zinc acetylacetone dispersion was obtained by dispersing zinc acetylacetone in a mixed solvent, wherein the volume ratio of ethanol to acetone in the mixed solvent was 1:3, and the mass-volume ratio of zinc acetylacetone to the mixed solvent was 1g:120mL. The mixed raw material was added to a twin-screw extruder with a screw speed of 220rpm, an extrusion temperature of 235℃, and a die temperature of 225℃. After melt blending extrusion, cooling, and pelletizing, high-toughness modified PETG copolyester composite particles were obtained. The mass ratio of PETG resin particles, PCL-based thermoplastic polyurethane, modified cellulose nanocrystal pre-dispersed masterbatch, epoxy functionalized chain extender, carbodiimide anti-hydrolysis agent, antioxidant, and zinc acetylacetone was 80:8:20:0.5:0.1:0.4:0.12.

[0090] S4: High-toughness modified PETG copolyester composite particles are placed in the hopper of a precision single-screw wire extruder. The extrusion section temperature is set to 210℃, the die temperature to 235℃, and the screw speed to 40rpm. After the melt is extruded through a 2.0mm diameter round die, it enters a 30℃ constant temperature water bath for cooling and shaping to obtain wire. After removing surface moisture through a dehumidifying hot air drying device, it is vacuum dried at 60℃ for 8 hours. Then, the wire is wound up to obtain a high-toughness modified PETG copolyester composite material for 3D printing.

[0091] Example 4

[0092] This embodiment provides a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method. The preparation method specifically includes the following steps:

[0093] S1: Cellulose nanocrystals were vacuum dried at 70℃ for 18 h, then dispersed in anhydrous N-methylpyrrolidone to obtain a dispersion, wherein the mass-to-volume ratio of cellulose nanocrystals to anhydrous N-methylpyrrolidone was 1 g:30 mL; after shearing and dispersion at 8000 rpm for 20 min, maleic anhydride and 4-dimethylaminopyridine were added to obtain reaction solution A, wherein the mass ratio of maleic anhydride to cellulose nanocrystals was 0.1:1, and the mass ratio of 4-dimethylaminopyridine to maleic anhydride was 1:50. The reaction was mechanically stirred at 110℃ for 3 h under nitrogen protection; after washing four times alternately with anhydrous ethanol and acetone, centrifuged, and vacuum dried at 75℃ for 10 h, maleic anhydride-modified cellulose nanocrystals were obtained; Maleic anhydride-modified cellulose nanocrystals were redispersed in anhydrous N-methylpyrrolidone, with a mass-to-volume ratio of maleic anhydride-modified cellulose nanocrystals to anhydrous N-methylpyrrolidone of 1 g:45 mL. After ultrasonic dispersion for 15 min, ε-caprolactone monomer and stannous octoate catalyst were added to obtain reaction solution B, with a mass ratio of ε-caprolactone to maleic anhydride-modified cellulose nanocrystals of 1.5:1 and a mass ratio of stannous octoate to ε-caprolactone monomer of 1:600. The reaction was carried out under nitrogen protection at 120 °C with mechanical stirring for 6 h. After washing with anhydrous ethanol and acetone alternately four times, centrifuging, and vacuum drying at 70 °C for 18 h, the nanocrystals were obtained by grinding and passing through a 300-mesh sieve.

[0094] S2: PETG resin particles, polycaprolactone-grafted carboxylated cellulose nanocrystals, antioxidant 1010 and antioxidant 168 were premixed at a mass ratio of 100:25:0.2:0.15 to obtain a premix; the premix was fed into a co-rotating twin-screw extruder at a screw speed of 260 rpm, an extrusion temperature of 220℃, a die head temperature of 225℃, and vacuum exhaust was turned on at a vacuum exhaust pressure of -0.07 MPa. After melt extrusion, water cooling, pelletizing, and vacuum drying at 75℃ for 9 hours, modified cellulose nanocrystal predispersed masterbatch was obtained.

[0095] S3: PETG resin particles, PCL-based thermoplastic polyurethane, and modified cellulose nanocrystal pre-dispersed masterbatch were dried at 75°C for 7 hours and then mixed. The epoxy functionalized chain extender Joncryl® ADR 4468 and the carbodiimide anti-hydrolysis agent Stabaxol® P were added. 100 and antioxidant 1010 were mixed to obtain a mixed raw material. During the mixing process, a zinc acetylacetone dispersion was sprayed on. The zinc acetylacetone dispersion was obtained by dispersing zinc acetylacetone in a mixed solvent, wherein the volume ratio of ethanol to acetone in the mixed solvent was 1:3, and the mass-volume ratio of zinc acetylacetone to the mixed solvent was 1g:100mL. The mixed raw material was added to a twin-screw extruder with a screw speed of 250rpm, an extrusion temperature of 228℃, and a die temperature of 230℃. After melt blending extrusion, cooling, and pelletizing, high-toughness modified PETG copolyester composite particles were obtained. The mass ratio of PETG resin particles, PCL-based thermoplastic polyurethane, modified cellulose nanocrystal pre-dispersed masterbatch, epoxy functionalized chain extender, carbodiimide anti-hydrolysis agent, antioxidant, and zinc acetylacetone was 85:5:15:0.3:0.15:0.3:0.08.

[0096] S4: High-toughness modified PETG copolyester composite particles are placed in the hopper of a precision single-screw wire extruder. The extrusion section temperature is set to 220℃, the die temperature to 225℃, and the screw speed to 25rpm. After the melt is extruded through a 2.2mm diameter round die, it enters a 20℃ constant temperature water bath for cooling and shaping to obtain wire. After removing surface moisture with a dehumidifying hot air drying device, it is vacuum dried at 65℃ for 6 hours. Then, the wire is wound up to obtain a high-toughness modified PETG copolyester composite material for 3D printing.

[0097] Comparative Example 1

[0098] This comparative example provides a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method. The difference from Example 1 is that PCL-based thermoplastic polyurethane is not added in S3, and an equal mass of PETG resin particles is added. Other operating steps and process parameters are exactly the same as in Example 1.

[0099] Comparative Example 2

[0100] This comparative example provides a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method. The difference from Example 1 is that step S1 is omitted, and in S2, unmodified cellulose nanocrystals are used to replace polycaprolactone-grafted carboxylated cellulose nanocrystals. Other operation steps and process parameters are exactly the same as in Example 1.

[0101] Comparative Example 3

[0102] This comparative example provides a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method. The difference from Example 1 is that zinc acetylacetone is not added in S3, and an equal mass of PETG resin particles is added. Other operating steps and process parameters are exactly the same as in Example 1.

[0103] Comparative Example 4

[0104] This comparative example provides a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method. The difference from Example 1 is that no epoxy functionalized chain extender is added in S3, and an equal mass of PETG resin particles is added. Other operating steps and process parameters are exactly the same as in Example 1.

[0105] Comparative Example 5

[0106] This comparative example provides a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method. The difference from Example 1 is that maleic anhydride and 4-dimethylaminopyridine treatment are not performed in S1. Instead, vacuum-dried cellulose nanocrystals are directly dispersed in anhydrous N-methylpyrrolidone, and ε-caprolactone monomer and stannous octoate are added to carry out a ring-opening grafting reaction to obtain polycaprolactone-grafted cellulose nanocrystals. In S2, the polycaprolactone-grafted cellulose nanocrystals are used to replace the polycaprolactone-grafted carboxylated cellulose nanocrystals in Example 1 by the same mass. Other operation steps and process parameters are exactly the same as in Example 1.

[0107] Comparative Example 6

[0108] This comparative example provides a high-toughness modified PETG copolyester composite material for 3D printing and its preparation method. The difference from Example 1 is that the S2 pre-dispersion masterbatch preparation step is omitted. Instead, PETG resin particles, polycaprolactone-grafted carboxylated cellulose nanocrystals, antioxidant 1010, antioxidant 168, PCL-based thermoplastic polyurethane, epoxy functionalized chain extender, carbodiimide anti-hydrolysis agent, antioxidant, and zinc acetylacetone dispersion are directly added to the twin-screw extruder in S3 for melt blending and extrusion. Other operating steps and process parameters are exactly the same as in Example 1.

[0109] The performance of the high-toughness modified PETG copolyester composite materials used for 3D printing in Examples 1-4 and Comparative Examples 1-6 was tested, and the specific process is as follows:

[0110] The filaments obtained from each embodiment and comparative example were vacuum dried at 65°C for 6 hours and then printed on the same FDM printing equipment. The nozzle diameter was 0.4 mm, the nozzle temperature was 240°C, the heated bed temperature was 80°C, the layer height was 0.20 mm, the printing speed was 50 mm / s, the fill rate was 100%, and the printing ambient temperature was 23 ± 2°C. After all test samples were printed, they were placed at 23°C and 50% RH for 24 hours before testing.

[0111] Wire drawing length test: A dual-cylinder wire drawing test model was printed using the same printing parameters. The model consisted of two cylinders with a diameter of 8 mm, a height of 40 mm, and a center-to-center distance of 40 mm. During printing, the retraction distance was set to 3.0 mm, the retraction speed to 35 mm / s, and the idle speed to 150 mm / s. After printing, the total length of visible wire drawing between the two cylinders was measured. Three samples were printed repeatedly, and the average value was taken as the wire drawing length.

[0112] Notched impact strength test: Standard notched impact test specimens were printed using the wires obtained from the various embodiments and comparative examples. The specimen size was 80mm × 10mm × 4mm, the notch depth was 2mm, and the notch direction was perpendicular to the printing layer direction. Cantilever beam notched impact tests were conducted according to GB / T 1843-2008, with no less than 5 specimens per test group, and the average value was taken as the notched impact strength.

[0113] Z-direction tensile strength test: Tensile specimens were printed using the wire obtained from each embodiment and comparative example, with the tensile direction of the specimen perpendicular to the stacking direction of the printed layers. The specimens were prepared according to the form of small and medium-sized tensile specimens in GB / T 1040.2-2022, with the tensile speed set at 5 mm / min. Each group of tests consisted of no less than 5 specimens, and the average value was taken as the Z-direction tensile strength, which was used to evaluate the interlayer bonding and interlayer crack resistance of the printed layers.

[0114] Bending performance test: Bending specimens were printed using the wires obtained from each embodiment and comparative example. The specimen size was 80mm×10mm×4mm. Three-point bending test was performed according to GB / T 9341-2008, with a span of 64mm and a loading speed of 2mm / min. Each test group had no less than 5 specimens. The bending strength and bending modulus were recorded to evaluate the rigidity retention of the toughened modified material.

[0115] Warpage test: The wire obtained from each embodiment and comparative example was used to print a long strip sample with a size of 100mm×20mm×3mm and a fill rate of 100%. After printing and cooling to room temperature, the sample was placed on a horizontal glass plate, and the maximum warpage height H at the four corners of the sample was measured. The warpage was calculated according to the formula "Warpage = H / 100mm×100%". Each group of tests had no less than 5 samples, and the average value was taken as the warpage.

[0116] The test results are shown in Table 1.

[0117] Table 1. Performance test results of high-toughness modified PETG copolyester composites used for 3D printing in Examples 1-4 and Comparative Examples 1-6.

[0118]

[0119] From the test results of Example 1 and Comparative Example 1 in Table 1, it can be seen that without the addition of PCL-based thermoplastic polyurethane, the system lacks a flexible energy-absorbing phase. The structure formed by the PETG matrix and polycaprolactone-grafted carboxylated cellulose nanocrystals is relatively hard, lacking elastic deformation and energy dissipation paths under impact loads, thus reducing the notched impact strength. At the same time, the role of flexible segments in heat healing and stress buffering at the interlayer interface is weakened, making the interlayer more prone to cracking under tension, thus reducing the Z-direction tensile strength. Due to the reduction of the flexible phase, the melt elasticity decreases, the tendency to draw fibers at the nozzle weakens, and the fiber length decreases. The overall rigidity of the material increases, thus the flexural modulus increases, but due to the lack of a flexible energy-absorbing phase, the stress buffering during bending is insufficient, and the flexural strength does not increase and is slightly lower than that of Example 1. Meanwhile, the higher rigidity is beneficial for maintaining the shape of the printed part, and the warpage is slightly reduced.

[0120] As shown in Table 1, the test results of Example 1 and Comparative Example 2 reveal that using unmodified cellulose nanocrystals instead of polycaprolactone-grafted carboxylated cellulose nanocrystals results in a lack of PCL flexible segments to coat and bridge the surface of the cellulose nanocrystals. This leads to poor interfacial compatibility between the unmodified cellulose nanocrystals and PETG and PCL-based thermoplastic polyurethane, making them prone to agglomeration points and interfacial stress concentration points, thus reducing notched impact strength. Under interlayer stress, the unmodified cellulose nanocrystals are unable to effectively participate in interfacial bridging and interfacial contact fusion, making the interfacial interface more prone to debonding, thus reducing Z-direction tensile strength. Uneven dispersion of cellulose nanocrystals causes melt flow fluctuations and unstable nozzle discharge, increasing filament length. While agglomeration of rigid cellulose nanocrystals may increase local rigidity, it worsens overall interfacial bonding, leading to decreased flexural strength and a relatively high flexural modulus. Simultaneously, agglomeration and interfacial inhomogeneity exacerbate differences in cooling shrinkage, increasing the warpage of the printed parts.

[0121] From the test results of Example 1 and Comparative Example 3 in Table 1, it can be seen that without the addition of zinc acetylacetonate, the system lacks the interface regulation effect of low-dose zinc salt in the melt processing and interlayer thermal contact stages. The interfacial contact fusion and stress buffering capacity between PETG, PCL-based thermoplastic polyurethane, and polycaprolactone-grafted carboxylated cellulose nanocrystals are weakened, thus the Z-direction tensile strength decreases. Due to insufficient interlayer interface bonding, cracks are more likely to propagate along the interlayer or interface during impact, and the notched impact strength also decreases accordingly. After the absence of zinc acetylacetonate, the interlayer interface thermal contact fusion is insufficient, and the interlayer fusion and stress release after melt deposition are not sufficient, resulting in an increase in the wire drawing length. Insufficient interface bonding and interface regulation also reduce the interface force transmission efficiency under bending stress, thus reducing the bending strength and slightly decreasing the bending modulus. At the same time, the interlayer residual stress release is insufficient, and the warpage of the printed part increases after cooling.

[0122] As shown in Table 1, the test results of Example 1 and Comparative Example 4 reveal that without the addition of epoxy functionalized chain extender, there is a lack of effective reactive interfacial bridging between the PETG end groups, PCL-based thermoplastic polyurethane, and polycaprolactone-grafted carboxylated cellulose nanocrystals. The interfacial bonding between the flexible phase and the polycaprolactone-grafted carboxylated cellulose nanocrystals in the PETG matrix is ​​weakened, making the interface more prone to debonding under impact loads and reducing notched impact strength. The lack of end-group reaction and bridging by the epoxy chain extender at the interlayer interface results in insufficient interlayer bonding stability, leading to a decrease in Z-direction tensile strength. Due to insufficient interfacial bonding and decreased melt stability, uneven flow and filament dragging are more likely to occur during nozzle extrusion, increasing filament length. The reduced interfacial force transmission efficiency during bending forces leads to a decrease in both bending strength and bending modulus. Simultaneously, insufficient melt strength and interfacial stability increase dimensional fluctuations during printing and cooling, resulting in increased warpage.

[0123] As shown in Table 1, the test results of Example 1 and Comparative Example 5 indicate that, without treatment with maleic anhydride and 4-dimethylaminopyridine, ε-caprolactone was directly used to perform one-step ring-opening graft modification of cellulose nanocrystals. This resulted in the introduction of polycaprolactone flexible segments onto the surface of the cellulose nanocrystals, but lacked the carboxylation structure formed after maleic anhydride treatment. Consequently, the interfacial bonding between the polycaprolactone-grafted cellulose nanocrystals, the epoxy functionalized chain extender, and the polyester matrix was relatively insufficient. Under impact loads, the interfacial buffering and energy dissipation capabilities were affected, resulting in a notched impact strength lower than that of Example 1. During interlayer tension during printing, the role of modified cellulose nanocrystals in interfacial bridging and interlayer contact fusion was weakened, resulting in a Z-direction tensile strength lower than that of Example 1. During the low-shear filament breakage stage at the nozzle, the stability of interfacial bonding and melt support decreased, leading to a higher filament length than that of Example 1. During bending stress, the interfacial force transmission and structural support were insufficient, resulting in lower bending strength and bending modulus than that of Example 1. Simultaneously, the interlayer bonding and cooling shrinkage stability were affected, resulting in a higher warpage than that of Example 1.

[0124] As can be seen from the test results of Example 1 and Comparative Example 6 in Table 1, the S2 pre-dispersion masterbatch preparation step was not performed. Instead, polycaprolactone-grafted carboxylated cellulose nanocrystals and other components were directly added to S3 for one-time melt blending. This prevented the modified cellulose nanocrystals from forming a pre-dispersion state in PETG resin. In the complex melt system containing PCL-based thermoplastic polyurethane, epoxy functionalized chain extender, carbodiimide anti-hydrolysis agent, antioxidant, and zinc acetylacetonate, local insufficient dispersion or uneven interfacial bonding is more likely to occur. Due to the decreased dispersion uniformity and interfacial dissipation of modified cellulose nanocrystals, the notched impact strength is lower than that of Example 1; due to the insufficient bridging and supporting effect of modified cellulose nanocrystals in the interlayer interface, the Z-direction tensile strength is lower than that of Example 1; due to the impact of direct blending on melt flow continuity and nozzle discharge stability, the filament length is higher than that of Example 1; due to the decreased interfacial force transmission efficiency under bending stress, both the bending strength and bending modulus are lower than those of Example 1; at the same time, uneven local dispersion and uneven interlayer bonding increase the dimensional fluctuations during cooling and shrinkage, resulting in a higher warpage than that of Example 1.

[0125] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A high-toughness modified PETG copolyester composite material for 3D printing, characterized in that, The high-toughness modified PETG copolyester composite material is prepared from raw materials comprising the following mass ratio: PETG resin, PCL-based thermoplastic polyurethane, modified cellulose nanocrystal predispersed masterbatch, epoxy functionalized chain extender, carbodiimide anti-hydrolysis agent, antioxidant, and zinc acetylacetonate in a mass ratio of (80-90):(3-8):(10-20):(0.2-0.5):(0.1-0.2):(0.2-0.4):(0.03-0.12); The modified cellulose nanocrystal predispersed masterbatch is prepared from PETG resin particles, polycaprolactone-grafted carboxylated cellulose nanocrystals, antioxidant 1010 and antioxidant 168, wherein the mass ratio of PETG resin particles, polycaprolactone-grafted carboxylated cellulose nanocrystals, antioxidant 1010 and antioxidant 168 is 100:(20-30):(0.1-0.3):(0.1-0.3). The polycaprolactone-grafted carboxylated cellulose nanocrystals were prepared by the following method: cellulose nanocrystals were vacuum dried and dispersed in anhydrous N-methylpyrrolidone to obtain a dispersion. After shear dispersion, maleic anhydride and 4-dimethylaminopyridine were added to obtain reaction solution A, which was mechanically stirred under nitrogen protection. After washing with anhydrous ethanol and acetone alternately, centrifuging, and vacuum drying for a second time, maleic anhydride-grafted cellulose nanocrystals were obtained. The maleic anhydride-grafted cellulose nanocrystals were redispersed in anhydrous N-methylpyrrolidone, ultrasonically dispersed, and ε-caprolactone monomer and stannous octoate catalyst were added to obtain reaction solution B. After mechanical stirring under nitrogen protection, after washing with anhydrous ethanol and acetone alternately, centrifuging, and vacuum drying for a third time, the nanocrystals were ground and sieved to obtain polycaprolactone-grafted carboxylated cellulose nanocrystals.

2. The high-toughness modified PETG copolyester composite material for 3D printing according to claim 1, characterized in that, The PCL-based thermoplastic polyurethane is Pearlthane® 11T85; The epoxy functionalized chain extender is any one of Joncryl® ADR 4468, Joncryl® ADR 4368, Joncryl® ADR4400 or Joncryl® ADR 4380; The carbodiimide antihydrolysis agent is any one of Stabaxol® P 100, Stabaxol® P 200, or Stabaxol® I; The antioxidant is any one of antioxidant 1010, antioxidant 168, or antioxidant 1076.

3. A method for preparing a high-toughness modified PETG copolyester composite material for 3D printing as described in any one of claims 1-2, characterized in that, Includes the following steps: S1: Cellulose nanocrystals were vacuum dried and dispersed in anhydrous N-methylpyrrolidone to obtain a dispersion. After shear dispersion, maleic anhydride and 4-dimethylaminopyridine were added to obtain reaction solution A. The reaction was mechanically stirred under nitrogen protection. After washing with anhydrous ethanol and acetone alternately, centrifuging, and vacuum drying for a second time, maleic anhydride-modified cellulose nanocrystals were obtained. The maleic anhydride-modified cellulose nanocrystals were redispersed in anhydrous N-methylpyrrolidone and ultrasonically dispersed. ε-caprolactone monomer and stannous octoate catalyst were added to obtain reaction solution B. The reaction was mechanically stirred under nitrogen protection. After washing with anhydrous ethanol and acetone alternately, centrifuging, and vacuum drying for a third time, the nanocrystals were ground and sieved to obtain polycaprolactone-grafted carboxylated cellulose nanocrystals. S2: PETG resin particles, polycaprolactone-grafted carboxylated cellulose nanocrystals, antioxidant 1010 and antioxidant 168 are mixed and then melt-extruded to obtain modified cellulose nanocrystal predispersed masterbatch. S3: PETG resin particles, PCL-based thermoplastic polyurethane, modified cellulose nanocrystal pre-dispersed masterbatch, epoxy functionalized chain extender, carbodiimide anti-hydrolysis agent, antioxidant, and zinc acetylacetonate are mixed and then melt-blended and extruded to obtain high-toughness modified PETG copolyester composite particles. S4: The high-toughness modified PETG copolyester composite particles are extruded, cooled, dried and wound into wire to obtain a high-toughness modified PETG copolyester composite material for 3D printing.

4. The method for preparing a high-toughness modified PETG copolyester composite material for 3D printing according to claim 3, characterized in that, In S1, cellulose nanocrystals are vacuum dried at 60-80℃ for 12-24h and then dispersed in anhydrous N-methylpyrrolidone to obtain a dispersion, wherein the mass-to-volume ratio of cellulose nanocrystals to anhydrous N-methylpyrrolidone is 1g:(20-50)mL; after shearing and dispersion at 5000-10000rpm for 10-30min, maleic anhydride and 4-dimethylaminopyridine are added to obtain reaction solution A, wherein the mass ratio of maleic anhydride to cellulose nanocrystals is (0.03-0.15):1, and the mass ratio of 4-dimethylaminopyridine to maleic anhydride is 1:(20-100). The reaction is mechanically stirred at 100-115℃ for 2-4h under nitrogen protection, washed alternately with anhydrous ethanol and acetone 3-5 times, centrifuged, and vacuum dried at 60-80℃ for 8-12h to obtain maleic anhydride-modified cellulose nanocrystals.

5. The method for preparing a high-toughness modified PETG copolyester composite material for 3D printing according to claim 4, characterized in that, In step S1, the maleic anhydride-modified cellulose nanocrystals are redispersed in anhydrous N-methylpyrrolidone, wherein the mass-to-volume ratio of maleic anhydride-modified cellulose nanocrystals to anhydrous N-methylpyrrolidone is 1 g:(20-50) mL; after ultrasonic dispersion for 10-20 min, ε-caprolactone monomer and stannous octoate catalyst are added to obtain reaction solution B, wherein the mass ratio of ε-caprolactone to maleic anhydride-modified cellulose nanocrystals is (0.8-2.0):1, and the mass ratio of stannous octoate to ε-caprolactone monomer is 1:(200-1000); under nitrogen protection, the reaction is mechanically stirred at 115-130℃ for 4-8 h, washed alternately with anhydrous ethanol and acetone 3-5 times, centrifuged, and vacuum dried at 60-80℃ for 12-24 h, then ground and passed through a 200-400 mesh sieve to obtain polycaprolactone-grafted carboxylated cellulose nanocrystals.

6. The method for preparing a high-toughness modified PETG copolyester composite material for 3D printing according to claim 3, characterized in that, In S2, PETG resin particles, polycaprolactone-grafted carboxylated cellulose nanocrystals, antioxidant 1010, and antioxidant 168 are premixed to obtain a premix. The premix is ​​fed into a co-rotating twin-screw extruder with a screw speed of 250-270 rpm, an extrusion temperature of 215-225℃, a die temperature of 220-230℃, and vacuum exhaust is activated with a vacuum exhaust pressure of -0.06~-0.09 MPa. After melt extrusion, water cooling, pelletizing, and vacuum drying at 70-80℃ for 8-10 hours, modified cellulose nanocrystal predispersed masterbatch is obtained.

7. The method for preparing a high-toughness modified PETG copolyester composite material for 3D printing according to claim 3, characterized in that, In S3, PETG resin particles, PCL-based thermoplastic polyurethane, and modified cellulose nanocrystal pre-dispersed masterbatch are dried at 70-80℃ for 6-8 hours and then mixed. Epoxy functionalized chain extender, carbodiimide anti-hydrolysis agent, antioxidant, and zinc acetylacetonate are added and mixed to obtain a mixed raw material. The zinc acetylacetonate is added in the form of a zinc acetylacetonate dispersion, which is obtained by dispersing zinc acetylacetonate in a mixed solvent. The volume ratio of ethanol to acetone in the mixed solvent is 1:3, and the mass-volume ratio of zinc acetylacetonate to the mixed solvent is 1g:(80-120)mL.

8. The method for preparing a high-toughness modified PETG copolyester composite material for 3D printing according to claim 7, characterized in that, In step S3, the mixed raw materials are added to a twin-screw extruder with a screw speed of 220-280 rpm, an extrusion temperature of 220-235℃, and a die temperature of 225-240℃. After melt blending extrusion, cooling, and pelletizing, high-toughness modified PETG copolyester composite particles are obtained.

9. The method for preparing a high-toughness modified PETG copolyester composite material for 3D printing according to claim 3, characterized in that, In S4, high-toughness modified PETG copolyester composite particles are placed in the hopper of a precision single-screw wire extruder. The extrusion section temperature is set to 210-235℃, the die temperature to 220-235℃, and the screw speed to 15-40 rpm. After the melt is extruded through a die with a diameter of 2.0-2.5 mm, it enters a constant temperature water bath at 15-30℃ for cooling to obtain wire. After removing surface moisture through a dehumidifying hot air drying device, it is vacuum dried at 60-70℃ for 4-8 hours. Then, the wire is wound up to obtain a high-toughness modified PETG copolyester composite material for 3D printing.

Citation Information

Patent Citations

  • Preparation method of polycaprolactone / nanocellulose crystal composite material

    CN106009571A

  • Basic production formula for preparing amorphous copolyester PETG by using recycled PET plastic and process method thereof

    CN112608454A